ANALISIS PELAKSANAAN RAHN DALAM GADAI SAWAH DI DESA SALOHE KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - M, Rahmaniar; Khalid, Idham (Jurnal Ar-Ribh, 2020)
The pawn contract practice conducted by the community in Salohe Village, East Sinjai District, Sinjai Regency is a rice field pawning. This research is focused to further study whether the practice of paddy pawning which has been carried out by the people of Salohe Village is in accordance with the Shariah economic principles. The problems studied are focused on the understanding of the people of Salohe Village regarding the implementation of paddy pawning and the application of Sharia principles in the implementation of paddy pawning in Salohe Village, East Sinjai District, Sinjai Regency. The method in this research is a qualitative approach. With the data source used is prime data, secondary data and informant data. Data collection uses observation, interviews and documentation. To analyze data, researchers used Data Reduction, Data Presentation and Conclusion Drawing / verification. The results obtained from this study of the implementation of paddy pawning in Salohe Village, Sinjai Timur District, Sinjai Regency were done long ago because of very urgent needs. The pawn process is only done verbally, namely the pawners (rahin) come to the murtahin to offer their fields to be pawned with the intention of obtaining some money. The power / use of rice fields is in the hands of the pawning recipient (murtahin) until the repayment of debt. Generally done interpersonal, which is inseparable from the spirit please help. However, the majority of them do not understand the pawn rules in Islam.